At the back of beyond - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
At the back of beyond, The Economist, October 1999 Mobiles have become a powerful tool for bringing the poor and isolated into the global economy.